MRI findings in lumbar spine following O2–O3 chemiodiscolysis: A long-term follow-up. Issue 4 (August 2017) - Bruno, Federico; Smaldone, Fernando; Varrassi, Marco; Arrigoni, Francesco; Barile, Antonio; Di Cesare, Ernesto; Masciocchi, Carlo; Splendiani, Alessandra
Intradiscal O2 –O3 injections are conventionally used as a minimally invasive treatment for lumbar disc herniation in patients not responding to conservative treatments. The aim of the present study is to report data of long-term imaging follow-up (3 years) of patients treated with intradiscal O2 –O3 lumbar chemiodiscolysis. We evaluated the changes of disc volume and the modifications in disc appearance (in terms of disc degeneration) and endplate changes (according to Modic), comparing the results with a control group of patients. Our results showed a stable reduction of the disc herniation volume in patients treated compared with the control group, while we did not find statistically significant differences in terms of disc degeneration and endplate changes (Modic). We concluded that the O2 –O3 discolysis, despite leading to a significant shrinkage of the disc herniation, does not involve – in the long term – biomechanical changes of the spine in terms of acceleration of the disc degeneration process in comparison with the natural course.